Substitute Addictions in Persons with Substance Use Disorders: A Scoping Review. (19th February 2021) - Sinclair, Deborah Louise; Sussman, Steve; Savahl, Shazly; Florence, Maria; Adams, Sabirah; Vanderplasschen, Wouter
Abstract: Background: Substitute addictions, addictive behaviors that sequentially replace each other's functions, have implications for recovery trajectories but remain poorly understood. We sought to scope the extent, range, and characteristics of research on substitute addictions in persons with substance use disorders. Method : Using Arksey and O'Malley's framework for scoping reviews, a systematic search was conducted to identify publications that referenced substitute addictions up to April 2018. Study characteristics were extracted and summarized to provide an overview of the extant literature. Results : The 63 included studies show that substitute addictions are terminologically and conceptually ambiguous. Much of the available literature is concentrated in developed contexts – and in particular the United States of America. While presentations varied, at least two sub-types of substitute addictions appeared: long-term replacement and temporary replacement. Existing theories suggest a multifactorial etiology. Conclusions : The findings suggest a strong need for: increased awareness of substitute addictions and its potential consequences for recovery; interventions that structure prevention and pre-, during-, and post-treatment interactions as well as future research to explore its nature and dynamics drawing on multiple methods.